Mechanisms of allergen-specific immunotherapy - Fujita, Hiroyuki (BioMed Central, 2012)
Allergen-specific immunotherapy (allergen-SIT) is a potentially curative treatment approach in allergic diseases. It has been used for almost 100 years as a desensitizing therapy. The induction of peripheral T cell tolerance and promotion of the formation of regulatory T-cells are key mechanisms in allergen-SIT. Both FOXP3(+)CD4(+)CD25(+ )regulatory T (Treg) cells and inducible IL-10- and TGF-β-producing type 1 Treg (Tr1) cells may prevent the development of allergic diseases and play a role in successful allergen-SIT and healthy immune response via several mechanisms. The mechanisms of suppression of different pro-inflammatory cells, such as eosinophils, mast cells and basophils and the development of allergen tolerance also directly or indirectly involves Treg cells. Furthermore, the formation of non-inflammatory antibodies particularly IgG4 is induced by IL-10. Knowledge of these molecular basis is crucial in the understanding the regulation of immune responses and their possible therapeutic targets in allergic diseases.